Improving children's e-safety skills through an interactive learning environment: a quasi-experimental study - Iolie Nicolaidou; Venizelou, Agnes (My University, 2020)
There is a worldwide concern for young children’s online safety and a growing necessity for e-safety skills to be taught to children from a young age as part of formal schooling. The purpose of this study was to design and evaluate the e ectiveness and motivational capacity of an interactive web-based learning environment for improving children’s e-safety skills. A quasi-experimental pre-test post-test control group design was used with an experimental group of 48 sixth-grade primary school students, who used the web-based learning environment over two 80-min lessons, and a control group of 25 students who did not. Findings revealed a statistically significant di erence (t(47) = 􀀀14.06, p < 0.01) in the experimental group students’ e-safety performance, when students’ pre-test scores (mean (M) = 41.13, SD = 10.47) were compared to their post-test scores (M = 56.69, SD = 9.38). The analysis of an attitudes questionnaire and of student interviews documented the experimental group students’ positive attitudes toward the learning environment. Findings provide evidence of the e ectiveness and motivational capacity of the web-based learning environment, which can be used in either formal education or informal learning settings, for improving children’s e-safety skills.
Keywords: E-safety skills; Children; Personal data protection; Avoiding hackers; Cyberbullying; Protection from malware; Multimedia; Interactive; Web-based learning environment